A Lightweight One-Stage Defect Detection Network for Small Object Based on Dual Attention Mechanism and PAFPN - Zhang, Yue; Xie, Fei; Huang, Lei; Shi, Jianjun; Yang, Jiale; Li, Zongan (Frontiers in Physics, 2021)
Normally functioning and complete printed circuit board(PCB) can ensure the safety and reliability of electronic equipment. PCB defect detection is extremely important in the field of industrial inspection. For traditional methods of PCB inspection, such as contact detection, are likely to damage the PCB surface and have high rate of erroneous detection. In recent years, methods of detection through image processing and machine learning have gradually been put into use. However, PCB inspection is still an extremely challenging task due to the small defects and the complex background. To solve this problem, we propose a lightweight one-stage defect detection network based on dual attention mechanism and Path Aggregation Feature Pyramid Network(PAFPN). At present, some methods of defect detection in industrial applications are often based on object detection algorithms in the field of deep learning. Through comparative experiments, compared with the Faster R-CNN and YOLO v3 which are usually used in the current industrial detection, the inference time of our method are reduced by 17.46 milliseconds(ms) and 4.75ms, and the amount of model parameters is greatly reduced. It is only 4.42 M, which is more suitable for industrial fields and embedded development systems. Compared with the common one-stage object detection algorithm Fully Convolutional One-Stage Object Detection (FCOS), mean Average Precision(mAP) is increased by 9.1%, and the amount of model parameters has been reduced by 86.12%.